STUDI POTENSI KEBANGKRUTAN PADA PERUSAHAAN INDUSTRI PROPERTI YANG GO PUBLIC DI BURSA EFEK INDONESIA - Muhammad Taufiq Abadi; Nunung Ghoniyah (Fakultas Ekonomi Universitas Islam Sultan Agung, 2016)
This study aims to determine and calculate the score of bankruptcy using Altman model, Springateand Zmijewski. In addition, this study also aims to analyze whether there are significant differencesof these models, as well as test the effect on stock prices in the property industry companies thatgo public on the stock exchange Indonesia. Variables used in this research is the Altman Z-Score,Springate methods, methods Zmijewski, bankruptcy prediction scores and stock prices. The samplesused were 34 property companies listed on the Indonesia Stock Exchange from 2013 to 2014 period.Sampling with purposive sampling technique. In this study, researchers used a method of analysisAltman Z-score, Springate and Zmijewski to test potential bankruptcy. Furthermore, using a differenttest engineering analysis Kruskal Wallis test and test the effect of using multiple regression with thehelp of Microsoft Excel program and the social science statistical package (SPSS) 20.0 VERSION.The results showed using Altman model there are 15 industrial firms potentially bankrupt property,Springate models there are 19 companies that could potentially bankrupt, while the model Zmijewskino company that could potentially bankrupt. In addition the results showed a significant differencebetween the analysis using a model Altman, Zmijewski Springate and in assessing the company’sbankruptcy in the property industry. Then the next research results showed that no significantrelationship between scores for bankruptcy against the company’s share price on the propertyindustry.Keywords: Altman Z-score, Springate and Zmijewski, bankruptcy and stock prices.